Publication Trends by Indonesia and Malaysia Affiliated Researchers About Public Policy, Technology, and Economics - Robertus In Nugroho Budisantoso; Sudi Mungkasi (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2020)
This paper aims to investigate the number of research articles authored by Indonesia and Malaysia affiliated researchers about three issues, namely, public policy, technology, and economics. We focus on articles indexed by Scopus in the ten year period 2010-2019. We obtain that Indonesia affiliated researchers are less productive from the beginning of the period. At the end of the period, Indonesia affiliated researchers produce more number of articles published internationally for public policy, technology, and economics issues. Furthermore, in total for any topics at the end of the period, Indonesia affiliated researchers publishes more articles. However, if we observe the number of published research articles with respect to the number of population, Indonesia’s is still left behind Malaysia’s.